Formulation of nanoemulsion parijoto fruit extract (Medinilla Speciosa) with variation of tweens stabilizers - Ananingsih, Victoria Kristina; Pratiwi, Alberta Rika; Soedarini, Bernadeta; Putra, Yohanes Alan Sarsita (Frontiers in Nutrition, 2024)
Nanotechnology has substantial potential for development due to its ability to modify surface characteristics and particle size, facilitating enhanced absorption of functional food compounds and controlled release of active substances to mitigate adverse effects. Nanoemulsion, a stable colloidal system formed by blending oil, emulsifier, and water, was identified as nanotechnology with promising applications. However, investigations into the impact of surfactants on characteristic nanoemulsions need to be more varied. This research gap necessitated further exploration in the advancement of nanotechnology-based foods. The parijoto fruit (Medinilla speciosa), an indigenous plant species in Indonesia, has yet to undergo extensive scrutiny for its potential use as a functional and nutraceutical food. Anthocyanins, a principal compound in the parijoto fruit, had exhibited efficacy in reducing the risk of cardiovascular disease diabetes, demonstrating anti-inflammatory and antioxidant properties. This study aimed to investigate the characteristics of nanoemulsion formulations derived from parijoto fruit extract and to evaluate an optimum condition with various tween surfactants. The findings from this investigation could furnish valuable insights for the further advancement of anthocyanin nanoemulsions from parijoto fruit extract. The results comprised the characterization of nanoemulsion particle size, polydispersity index, ζ-potential , conductivity, pH, and viscosity. Through mathematical modelling and statistical methods, RSM optimizes nanoemulsion by examining the relationships and interactions between independent and response variables.Furthermore, the characterization of nanoemulsion encompassed ζ-potential , polydispersity, particle size, conductivity, pH, and viscosity. Elevated surfactant concentrations resulted in diminished particle sizes and more uniform size distribution, albeit reaching a plateau where surfactant aggregation and micelle formation ensued. Increased concentrations of surfactant type, concentration, and parijoto extract impacted the physical characteristics of nanoparticle size and polydispersity. The optimal process conditions for nanoemulsion consisting of the type of Tween used are Tween 80, Tween concentration of 12 %, and parijoto fruit extract concentration of 7.5 %, yielding a desirability value of 0.74, categorizing it as moderate.